Solution processed oxygen and moisture barrier based on glass flakes for encapsulation of organic (opto-) electronic devices. (11th June 2021) - Channa, Iftikhar Ahmed; Distler, Andreas; Scharfe, Benedikt; Feroze, Sarmad; Forberich, Karen; Lipovšek, Benjamin; Brabec, Christoph J; Egelhaaf, Hans-Joachim
Abstract: The concept of transparent barriers against oxygen and water based on polymer films filled with glass flakes is presented. Barriers are prepared by casting polyvinyl butyral (PVB) films containing glass flakes of different aspect ratios (ARs) at different loadings to systematically study the effect of these parameters on barrier quality and optical transmission. It is found that the glass flakes are distributed homogeneously in the PVB film, with an almost perfect orientation of the long axes of the platelets parallel to the film surface. For glass flakes having an AR of 2000, barrier films with optical transmittance exceeding 85% and water vapor transmission rates of 0.14 g m −2 d −1 are obtained at a glass loading of 25 vol%. The haze of the glass flake filled PVB films, which is mainly due to surface roughness of the films according to optical simulations, is reduced by coating a smoothing layer on top. The barrier properties persist even after 20 000 cycles of bending at a radius of 3 cm. The lifetime of organic solar cells increases to beyond 1000 h under damp heat conditions as well as under constant illumination, when the devices are encapsulated with the PVB/glass flake composite films.